2019
DOI: 10.1002/jssc.201900438
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic solid‐phase extraction of tobacco‐specific N‐nitrosamines using magnetic graphene composite as sorbent

Abstract: Tobacco‐specific N‐nitrosamines are carcinogenic components in mainstream cigarette smoke. To explore tobacco‐specific N‐nitrosamine release levels in cigarettes, a magnetic solid‐phase extraction procedure using magnetic graphene composite as sorbent for fast enrichment of tobacco‐specific N‐nitrosamine was developed. Under optimal conditions, a tobacco‐specific N‐nitrosamine determination method was successfully proposed by combining magnetic solid‐phase extraction procedure and high‐performance liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…[98a,99] While most investigations have focused on aqueous pollutants, some studies have reported the adsorptive removal of hazardous substances from the gas phase, [98c] particularly hazardous substances from cigarette smoke (Figure 9d,e). [100] Graphene mainly relies on 𝜋-𝜋 interaction to adsorb NNK. [101] Figure 8.…”
Section: Graphenementioning
confidence: 99%
“…[98a,99] While most investigations have focused on aqueous pollutants, some studies have reported the adsorptive removal of hazardous substances from the gas phase, [98c] particularly hazardous substances from cigarette smoke (Figure 9d,e). [100] Graphene mainly relies on 𝜋-𝜋 interaction to adsorb NNK. [101] Figure 8.…”
Section: Graphenementioning
confidence: 99%
“…Although the oncogenic mechanisms of NNK remain debatable, one possible mechanism is that the metabolic products of NNK are capable of forming adducts with DNA. TSNAs are formed during the growth, curing, storage, and processing of tobacco leaves. The determination of TSNA concentration during the postharvest period of tobacco can be used for the quality control of tobacco products. An efficient determination method of TSNAs is based on LC/GC–MS/MS along with preconcentration steps. The preconcentration of TSNAs using an efficient and selective adsorbent is important, especially for samples with a complex matrix and/or low concentration of TSNAs. Moreover, the efficient adsorbent for TSNAs can also be used to extract TSNAs from tobacco waste to reduce the disposal of carcinogenic species into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, several adsorbents for TSNAs have been developed based on inorganic porous compounds, graphene aerogels, and imprinted polymers. , However, the removal efficiencies for TSNAs are low (the maximum adsorption capacity for NNK is usually lower than 70 mg/g). Therefore, efficient and selective adsorbents for TSNAs are still highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, MSPE has received significant attention in the past few years. In this method, an external magnetic field is used for separating the analytes adsorbed on the magnetic nanoparticles (MNPs) from a solution [8–10]. In 1973, Robinson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many MNPs have been used in MSPE. In recent studies carbon‐based MNPs such as carbon nanotubes [14, 15], graphene [10, 16], phenyl [17], fluorenyl [18], porous β‐cyclodextrin polymer [19], C 8 [20], and C 18 [21] were used as sorbents because of their high adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%